HIBISCUS LEAF MUCILAGE AS STABILISER FOR PHARMACEUTICAL DISPERSE SYSTEMS - Ash, Dipanjana; Ghosh, Priyanka; Biswas Masjee, Sutapa; Roy Biswas, Gopa (International Journal of Applied Pharmaceutics, 2019)
Objective: Stable pharmaceutical disperse systems are defined as heterogeneous, biphasic systems as suspensions and emulsions, stabilized by third agent or stabilizer. The aim of the present investigation was to extract mucilage from the leaves of Hibiscus rosa-sinesnsis L. and explore its ability to function as stabiliser for adult (10%w/v) and paediatric (2.4%w/v) paracetamol (PCM) suspensions and 2% v/v sunflower oil emulsions. Methods: Isolated mucilage powder was subjected to phytochemical tests to identify the major phytochemical constituents, FTIR spectroscopy to establish compatibility with formulation ingredients, X-ray diffractometry to determine the crystalline nature and viscosity study by Ostwald viscometer and swelling behaviour in water to determine the swelling index. Results: Qualitative phytochemical screening of the mucilage (HM) revealed the presence of non-reducing sugars, gums and mucilage. HM possesses a highly amorphous structure with extremely low overall crystallinity. The mucilage belongs to the class of carbohydrate as it contains–OH groups with intermolecular hydrogen bonding, with 1→4 glycosidic bonds which accounts for its high hydration capacity. Swelling index and relative viscosity of 0.5% w/v mucilage in water was found to be 1050 and 4.84 respectively at 25 °C. Although adult PCM suspensions containing 4% w/v mucilage exhibited poor redispersibility, paediatric suspension containing 1 and 2% w/v mucilage showed gradual settling of particles with good re-dispersibility and flowability. Emulsion activity index (EAI) values of the three emulsions (0.5, 0.75 and 1%w/v HM) were found to be close to 2 g. m-1 ml-1suggesting concentration independent activity of HM as an emulsifier. Emulsion stability index (ESI) values at 72 h showed comparatively less stability with increasing concentration of mucilage probably due to polysaccharide chain overlapping at high concentration leading to less effective surface coverage per unit gum concentration. Conclusion: Therefore, hibiscus leaf mucilage has the capacity to stabilize a suspension or emulsion based on its capacity to adsorb onto solid or liquid interfaces.